Arbitration and collective bargaining : conflict resolution in labor relations - Prasow, Paul.; Peters, Edward (New York : McGraw-Hill, 1970)
The book focuses on the decision-making function of the arbitrator and on the dynamics of the arbitration process as an integral part of the larger institution of collective bargaining in the United States. It seeks to throw light on those fundamental questions which face any adjudicator, arbitrator or judge, whose pervasive influence is felt by the parties in crucial areas of their bargaining relationships.
Includes index.
Includes bibliographical references: p. 396-412.
rpm 20/03/2018
Loans
Keywords: Arbitration, Industrial; Collective bargaining